2018
DOI: 10.1002/dvdy.24629
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal cell adhesion molecule (NrCAM) is expressed by sensory cells in the cochlea and is necessary for proper cochlear innervation and sensory domain patterning during development

Abstract: NrCAM is expressed by several neural and sensory epithelial subtypes within the developing cochlea, and the loss of Nrcam confers numerous, but nonpermanent, developmental defects in innervation and sensory domain patterning. Developmental Dynamics 247:934-950, 2018. © 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 75 publications
2
16
0
Order By: Relevance
“…1). Previously, we documented how cochlear morphology and ribbon synapse distribution were able to "recover" in NrCAM Ϫ/Ϫ mice (Harley et al, 2018) and a similar kind of recovery in the Sema5b Ϫ/Ϫ mice may lead to limited changes in adult hearing thresholds. Our hearing assessment was underpowered to detect very subtle differences in hearing thresholds or wave I amplitude, and it is possible that slight differences may be detected with a larger cohort of mice in which males and females are analyzed separately (Milon et al, 2018).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…1). Previously, we documented how cochlear morphology and ribbon synapse distribution were able to "recover" in NrCAM Ϫ/Ϫ mice (Harley et al, 2018) and a similar kind of recovery in the Sema5b Ϫ/Ϫ mice may lead to limited changes in adult hearing thresholds. Our hearing assessment was underpowered to detect very subtle differences in hearing thresholds or wave I amplitude, and it is possible that slight differences may be detected with a larger cohort of mice in which males and females are analyzed separately (Milon et al, 2018).…”
Section: Discussionmentioning
confidence: 83%
“…We next assessed general patterns of cochlear innervation in Sema5b Ϫ/Ϫ and littermate control cochleae using anti-NF200 antibodies, which preferentially label SGNs (Harley et al, 2018) and anti-GAP43 antibodies, which preferentially label efferent fibers (Simmons et al, 1996). Previously, we showed high-magnification micrographs demonstrating that NF200 and GAP43 antibodies clearly delineate these different classes of fibers in the early postnatal cochlea (Harley et al, 2018). As shown in Figure 4, H and I, the SGN radial bundles and fibers contacting the IHCs (type I SGNs) were similar in the Sema5b Ϫ/Ϫ and control cochleae.…”
Section: Sema5b Is Required For Normal Sgn Branchingmentioning
confidence: 99%
“…10, Supplementary Data 11). This list contained genes that were known to be expressed in LPsCs, including Prox1, Bmp2, Ngfr, and Nrcam 39,40,42,43 , and additional markers, including Tgfβr1, Fzd9 (Frizzled9), Elmo1, and Lsamp ( Fig. 5a, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…pruning (Harley et al, 2018). RNA sequencing data failed to detect NrCAM transcripts in the chicken BP at E6 (Munnamalai et al, 2017), although this time point precedes synapse formation in this organ.…”
Section: Semaphorin Signaling Genes In the Hcs Suggest A Role In Symentioning
confidence: 89%
“…Based on the timing of the expression we observe, Sema3D, Sema3F , and PlxnA1 may be involved in synapse formation in the BP. Neuronal cell adhesion molecule (NrCAM) has been shown to associate with Nrp2 (Julien et al, ) and recent work in the mouse inner ear has shown that it is involved in limiting ribbon synapses in the HCs, likely through inhibiting synapse formation or promoting pruning (Harley et al, ). RNA sequencing data failed to detect NrCAM transcripts in the chicken BP at E6 (Munnamalai et al, ), although this time point precedes synapse formation in this organ.…”
Section: Discussionmentioning
confidence: 99%